Polarization Agile Reconfigurable Rectangular Patch Antenna for Biomedical Applications - Manavalan, Saravanan; Shankarlal, Balraj; Prakash, Veeraswamy Radhakrishnan; Eswaramoorthy, Sathish; Rajmohan, Madasamy (Applied Computational Electromagnetics Society Journal (ACES), 2024)
A polarization agile patch antenna resonating at 2.4 GHz ISM band is presented. The antenna is based on a rectangular radiating element along with reconfigurable parasitic patches located at its periphery of the radiating element. Two switching diodes are used to reconfigure the geometry of the radiating element. Upon proper biasing of the switching diodes the antenna attains linear or circular (LHCP/RHCP) polarization states. The entire antenna is modelled using a high-frequency structure simulator and is validated using an Agilent network analyser (N9925A) and antenna test systems for measuring impedance and radiation characteristics. Over the entire operating band, the antenna shows better impedance matching and achieves −10 dB impedance bandwidth of 100 MHz (2.40-2.5 GHz) in linear state and 85 MHz (2.41-2.495 GHz) in the circularly polarization states along with peak gain of 5.61 dBi for LP state and 4.98 dBi for CP state in the operatingrange.